Improvising a Music-Theory Curriculum - Michaelsen, Garrett (Critical Studies in Improvisation / Études critiques en improvisation)

(untitled) (University of Guelph College of Arts, 2022)
This article explores the cultural hegemonies perpetuated by typical music-theory curricula and advocates for the use of improvisation—as both classroom activity and guiding philosophy—as a way forward.